Women's mode of birth preferences and preparedness of hospitals to support vaginal birth in the public health sector in Argentina - Perrotta, Carla (2022)
Background: This paper reports on postpartum women's mode of birth (MOB) preferences across five public maternity hospitals in Argentina, the variables and motives associated with those preferences, and hospital services preparedness. Methods: A cross‐sectional study was conducted with postpartum women aged 15 years or older in geographically diverse public hospitals in Argentina between November 2018 to June 2019. Data on obstetric history, companionship, and MOB preference and motives were collected from mothers using a semistructured interviewer‐administered questionnaire. Hospital and participant characteristics, MOB preferences, and perceived advantages and disadvantages were described. Associations between vaginal birth preference, participant characteristics, and hospitals were assessed using odds ratios generated from mixed‐effect logistic regression analyses. Results: The sample included 621 postpartum women, 60% of whom had a vaginal birth. In three of the participating hospitals, most women indicated vaginal birth as their preferred MOB (90%); however, the preference for a vaginal birth was lower in the remaining two hospitals (67%). Differences in preferences across hospitals remained after adjusting by women's age or obstetric history. Cited motives for vaginal birth preference included faster recovery, feeling ready for a vaginal birth, and considering it a more natural process. Preference for a caesarean birth was based on perceptions of increased safety and avoiding pain. Conclusions: The characteristics of obstetric services revealed they are prepared for obstetric emergencies but have limited resources and support to sustain the process of vaginal birth. Despite the limited support, women giving birth in public maternity hospitals preferred vaginal delivery to a caesarean section. This study could not identify hospital variables associated with women's birth preferences across hospitals.